Hubungan Religiusitas dengan Subjective Well-Being pada Lansia di Jakarta - Muhammad Akhyar; Ratu Ifthiharfi; Viana Wahyuni; Milsa Ardhani Putri; Vannisa Yunita Putri; Wildayati Wildayati; Muhammad Rafly (Jurnal Ilmiah Psikologi MIND SET, 2019)
This study aimed to look at the relationship between religiosity and subjective well-being (consisting of life satisfaction, positive emotions and negative emotions) in the elderly in Jakarta (N = 73). The measurement of religiosity in this study use an adaptation of the Religiosity Scale (Diduca & Joseph, 2007), while to measure life satisfaction, and the level of positive and negative emotions using The Satisfaction with Life Scale (Diener, Emmons, Larsen, & Griffin, 1985) and Positive Affect and Negative Affect Scale (Watson, Clark, & Tellegan, 1988). The results showed there was a relationship between life satisfaction and positive emotions with religiosity (r = 0.423, p <0.05, r = 0.234, p <0.05), but religiosity did not have a significant relationship with negative emotions (r = 0.048, p> 0.05). The results also found that as age increases, the relationship between religiosity and subjective well-being strengthens.